Contribution of the ATP Binding Site of ParE to Susceptibility to Novobiocin and Quinolones in Streptococcus pneumoniae - Dupont, Philippe (American Society for Microbiology, 2005)
In Streptococcus pneumoniae, an H103Y substitution in the ATP binding site of the ParE subunit of topoisomerase IV was shown to confer quinolone resistance and hypersensitivity to novobiocin when associated with an S84F change in the A subunit of DNA gyrase. We reconstituted in vitro the wild-type topoisomerase IV and its ParE mutant. The ParE mutant enzyme showed a decreased activity for decatenation at subsaturating ATP levels and was more sensitive to inhibition by novobiocin but was as sensitive to quinolones. These results show that the ParE alteration H103Y alone is not responsible for quinolone resistance and agree with the assumption that it facilitates the open conformation of the ATP binding site that would lead to novobiocin hypersensitivity and to a higher requirement of ATP.